Perilaku Makan Orangutan Tapanuli (Pongo tapanuliensis) di Stasiun Penelitian Camp Mayang Batang Toru, Sumatera Utara - Nurhayani Br Sitepu; Melfa Aisyah Hutasuhut; Kartika Aisyah Manalu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the number of individuals, daily behavior, diet types, and feeding methods of Tapanuli orangutans at the Camp Mayang Research Station, Batang Toru, North Sumatra. The method used was focal animal sampling. The results showed that four individual orangutans were identified: Cemara, Beta, Bittang, and Dona. The most dominant daily behavior was feeding behavior, with a percentage of 63.21%. The diet consumed included Agathis borneensis, Freycinetia excelsa, Koompassia excelsa, Lithocarpus rassa, Gironniera subaequalis, Cryptocarya crassinervia, Artocarpus maingayi, Spatholobus parviflorus, and Campnosperma squamatum, with fruit being the main part of the diet (68.04%) due to the frugivorous nature of the species. The most common feeding method was picking (68.02%). This study represents a conservation effort for Tapanuli orangutans, the world's rarest and most endangered orangutan species. Keywords: Diet Types, Tapanuli Orangutan, Feeding Behavior